Model Bisnis Industri Tambang Timah Berkelanjutan (Studi Kasus Bangka Belitung) - Irawan, R.Rudy; Sumarwan, Ujang; Suharjo, Budi; Djohar, Setiadi (Universitas Brawijaya, Indonesia, 2014)
Bangka Belitung province's economy has a very high dependence on the tin. BPS data of 2013 showed tin contributed 33.60% PDRB and expected of more than 70% if the multiplier effect applied (Megawandi, 2013). But the tin mining industry is currently facing complex problems including undeveloped downstream (Widyatmiko, 2012), environmental damage (Sapanli, 2009; Inonu, 2010; Walhi, 2013), illegal small scale mining (Elfida, 2007; Sapanli 2010), and overlap of licensing and laws (Purba, 2007; Hayati, 2011; Bastida and Paramita, 2013), social issues (Aziz and Salim, 2005; Zulkarnain et al 2005; Erman, 2007; Resosudarmo and Subiman, 2010), damage of the forest (Sidabukke, 2011) and other problems. This study aims to design a business model of tin mining industry in Bangka Belitung so the sustain able issues can be resolved. The methodology used in this study was in-depth structured interview of expertstakeholders. The results of the study showed a chart which was interrelated relationship between elements which were created and delivered value for the industry and the state. The study of tin business model is a flow chart of the mining process to the trade.